(untitled) (ModaPalavra e-periódico, 2011)
This article discusses the integration of sustainable design in product development with local identity. Products with local identity in itself carry sets of material and immaterial, and as part of a new approach to the role of the designer within the context of exploitation of specific features of a specific territory. In this perspective, there is the relational aspect of the territory, where it is circumscribed by the social relations made by individuals / actors of a society. In this sense, the design represents a catalyst for innovation and creating a positive image linked to territory, its products and services, resulting from a network that involves biodiversity resources, traditional modes of production, customs and consumer habits too. Allied to these facts is located the value chain strategy, based on the promotion and development of sustainable solutions, which can act in the setting of a systemic design integrated with the territory.